2019
DOI: 10.1038/s41433-019-0400-8
|View full text |Cite
|
Sign up to set email alerts
|

Graded Anderson procedure for correcting abnormal head posture in infantile nystagmus

Abstract: Purpose To describe the long-term results of Anderson procedure, which includes recession of the two extraocular yoke muscles responsible for eccentric eye position and abnormal head posture (AHP) in patients with infantile nystagmus. Methods Retrospective data collection of patients who underwent an Anderson procedure at a single medical center by one surgeon from 2008 to 2016. The main outcome measure was the elimination of AHP following surgery. Results Twenty-seven patients (18 males, 9 females) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…The efficacy of the Anderson procedure was later reported by various authors, though over-correction and limitation of ductions were reported following large amounts of recessions 5,16,59 . In a larger series of 27 patients (9 with OCA), Yahalom et al reported significant decrease in angle of AHP by average of 7.2° following surgery, with complete resolution in 14 patients 173 . The Anderson-Kestenbaum procedure is the standard surgical approach for AHP.…”
Section: B Management Of Nystagmus and Its Sequelaesmentioning
confidence: 95%
“…The efficacy of the Anderson procedure was later reported by various authors, though over-correction and limitation of ductions were reported following large amounts of recessions 5,16,59 . In a larger series of 27 patients (9 with OCA), Yahalom et al reported significant decrease in angle of AHP by average of 7.2° following surgery, with complete resolution in 14 patients 173 . The Anderson-Kestenbaum procedure is the standard surgical approach for AHP.…”
Section: B Management Of Nystagmus and Its Sequelaesmentioning
confidence: 95%
“…This posture can be a head turn along the horizontal or vertical axis, a head tilting, or a combination of these positions. If uncorrected, this abnormal head posture can lead to neck and spine issues, impairment of social interactions, and decreased quality of life ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In der Literatur sind auch nach niedriger dosierter AO bemerkenswerte Effekte beschrieben. Nicht selten war die KZH mit 45°angegeben, mehr als wir in der Regel fanden [28]. Nicht selten wurde trotz geringerer Rücklagerungsstrecken Vollkorrektur beschrieben, was in unserer Studie ebenfalls die Ausnahme war.…”
Section: Introductionunclassified
“…Ein falsch zu hoher Operationseffekt ergibt sich, wenn die KZH zwar präoperativ, aber nicht auch postoperativ unter maximaler Visusforderung bestimmt wird oder die KZH präoperativ überschätzt wurde. Bei 45°Kopfdrehung stellt sich die Frage, ob eine weit laterale Ruhezone vorliegt oder ob erst maximale Blickwendung den Nystagmus hemmt, erst recht in Fällen, bei denen eine Drehung von erstaunlichen 50°angegeben wird [28]. In diesem Fall der Beruhigung durch den seitlichen Anschlag ist eine Vollkorrektur der KZH trotz noch vorhandener Restmotilität schwer zu verstehen.…”
Section: Introductionunclassified